Fabrication of flexible silicon nanowires by self-assembled metal assisted chemical etching for surface enhanced Raman spectroscopy. Issue 96 (30th September 2016) - Kara, S. A.; Keffous, A.; Giovannozzi, A. M.; Rossi, A. M.; Cara, E.; D'Ortenzi, L.; Sparnacci, K.; Boarino, L.; Gabouze, N.; Soukane, S.
Abstract : Flexible silicon nanowires fabricated by nano spheres lithography and metal assisted chemical etching for surface enhanced Raman spectroscopy. Abstract : A homogenous array of flexible gold coated silicon nanowires was fabricated by the combination of nano spheres lithography and metal assisted chemical etching to obtain highly effective Surface Enhanced Raman Spectroscopy (SERS) substrates. 3D nanostructures with different aspect ratios and well-defined geometries were produced by adjusting the fabrication parameters in order to select the best configuration for SERS analysis. The optimum flexible nanowires with an aspect ratio of 1 : 10 can self-close driven by the microcapillary force under exposure to liquid and trap the molecules at their metallic coated "fingertips", thus generating hot spots with ultrahigh field enhancement. The performance of these SERS substrates was evaluated using melamine as the analyte probe with various concentrations from the millimolar to the picomolar range. Flexible gold coated SiNWs demonstrated high uniformity of the Raman signal over large area with a variability of only 10% and high sensitivity with a limit of detection of 3.20 × 10 −7 mg L −1 (picomolar) which promotes its application in several fields such food safety, diagnostic and pharmaceutical. Such an approach represents a low-cost alternative to the traditional nanofabrication processes to obtain well ordered silicon nanostructures, offering multiple degrees of freedom in the design of different geometries such as inter-wire distance, density of the wires on the surface as well as their length, thus showing a great potential for the fabrication of SERS substrates.